2016
DOI: 10.1002/cncy.21777
|View full text |Cite
|
Sign up to set email alerts
|

Young investigator challenge: The morphologic analysis of noninvasive follicular thyroid neoplasm with papillary‐like nuclear features on liquid‐based cytology: Some insights into their identification

Abstract: KEY WORDS: Liquid-based cytology; noninvasive follicular variant of papillary thyroid cancer; noninvasive follicular thyroid neoplasm with papillary-like nuclear features; thyroid carcinoma; thyroid lesions. INTRODUCTIONOver the last decades, the exact nature of thyroid lesions diagnosed as follicular variant of papillary thyroid carcinoma (FVPTC) has been debated. [1][2][3][4][5][6][7][8] Specifically, FVPTCs appear to represent a heterogeneous group of carcinomas and a controversial entity including both enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
150
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(169 citation statements)
references
References 38 publications
15
150
2
2
Order By: Relevance
“…This data could also have a significant impact on the cytological evaluation of thyroid nodules in the differential diagnosis of NIFTPs versus EFVPTCs. In fact this is in agreement with the data from Maletta et al and Bizzarro et al, who concluded that the majority of these NIFTPs are diagnosed as indeterminate lesions (Bizzarro et al, 2016, Maletta et al, 2016) on cytological samples. In this way, the data provided by Fu et al on PD-L1 as useful marker in the discrimination between EFVPTC and NIFTP on histology could be also helpful on cytology, with important implications in clinical and surgical assessment and in lowering of the possible overtreatment.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This data could also have a significant impact on the cytological evaluation of thyroid nodules in the differential diagnosis of NIFTPs versus EFVPTCs. In fact this is in agreement with the data from Maletta et al and Bizzarro et al, who concluded that the majority of these NIFTPs are diagnosed as indeterminate lesions (Bizzarro et al, 2016, Maletta et al, 2016) on cytological samples. In this way, the data provided by Fu et al on PD-L1 as useful marker in the discrimination between EFVPTC and NIFTP on histology could be also helpful on cytology, with important implications in clinical and surgical assessment and in lowering of the possible overtreatment.…”
supporting
confidence: 93%
“…This is also supported by the fact that NI-FVPCs, recently termed as NIFTPs, and invasive FVPT (I-FVPC), also known as encapsulated follicular variant of papillary thyroid carcinoma (EFVPTC), are not prognostically and molecularly alike (Bizzarro et al, 2016, Chen et al, 2012, Ganly et al, 2015, Liu et al, 2006, Lloyd et al, 2004, Maletta et al, 2016, Nikiforov et al, 2016, Ustun et al, 2014) as clearly assessed by several scientific reports demonstrating that I-FVPCs show more frequent lymph nodes metastases, recurrences and prevalence of BRAF mutations whilst NI-FVPCs (accounting for 50%–70% of the entire subset of FVPCs) show a more favorable outcome (Nikiforov et al, 2016). According to the paper by Nikiforov et al, this new entity was defined by an encapsulated nodule with a follicular architecture and a set of morphological features of PTC (including nuclear membrane irregularities, ground glass appearance of the nuclei, larger nuclear size) (Nikiforov et al, 2016).…”
mentioning
confidence: 96%
“…Noninvasive encapsulated follicular variant of papillary thyroid carcinoma (NE‐FVPTC) was recently reclassified as NIFTP . As shown in the second edition of the Bethesda thyroid system, this new terminology has decreased the ROM in most of the TBSRTC categories, most significantly in the indeterminate categories . Some studies have demonstrated that NIFTP can indeed be differentiated from PTC in cytological samples .…”
Section: Niftp and Molecular Testingmentioning
confidence: 99%
“…Brandler et al16 found that when PTC nuclear features and microfollicles are present NIFTP should be considered. Bizzarro et al13 concluded that NIFTP usually lacks pseudoinclusions and papillary structures; nuclear size and microfollicular clusters may allow differentiation between NIFTP and invasive FVPTC. Howitt et al17 found statistically significant differences in cytomorphologic features between patients with NIFTP and those with PTC.…”
Section: Introductionmentioning
confidence: 99%